Intestinal obstruction due to congenital mesenteric band in an adult patient - YEGEN, ŞEVKET CUMHUR (TURKISH SOC GASTROENTEROLOGY, 2013)
We report the case of a 30-year-old male patient who was admitted to the Emergency Department with symptoms and signs of intestinal obstruction. There was no history of abdominal surgery or trauma. Abdomen was distended. Abdominal plain X-ray showed intestinal loops with air-fluid levels in the middle area of the abdomen. Computed tomography showed small bowel dilatation and free fluid in the abdomen. A laparotomy was subsequently performed and the intraoperative findings revealed a band extending from the root of the mesentery to the antimesenteric wall of the jejunum. The band was resected; the postoperative course was uneventful. Congenital bands are extremely rare and usually observed in childhood. This case, therefore, represents an unusual surgical problem in an older individual in whom the diagnosis was clinically unexpected.
Keywords: Mesenteric band; intestinal obstruction; adult; SMALL-BOWEL OBSTRUCTION